Race mixture in nineteenth-century U.S. and Spanish American fictions : gender, culture, and nation building - Rosenthal, Debra J., 1964- (Chapel Hill : University of North Carolina Press, 2004)
Race mixture has played a formative role in the history of the Americas, from the western expansion of the United States to the political consolidation ofLatin America. This text examines 19th-century authors in the United States and Spanish America who struggled to give voice to contemporary dilemmas about interracial sexual and cultural mixing.
Race mixture and the representation of Indians in the United States and the Andes -- Temperance and miscegenation in Whitman's Franklin Evans -- Cuban slave fiction : race mixture in Sab -- Floral counterdiscourse : miscegenation, ecofeminism, and hybridity in Lydia Maria Child's Romance of the republic -- The white blackbird : miscegenation, genre, and the tragic mulatta in Howells, Harper, and The babes of romance.
Includes bibliographical references (pages 157-177) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Nervo, Amado; Lateinamerika; Universidad Sergio Arboleda; American fiction -- 19th century -- History and criticism; Miscegenation (Racist theory) in literature; Spanish American fiction -- 19th century -- History and criticism; Comparative literature -- American and Spanish American; Comparative literature -- Spanish American and American; Multiracial people in literature; Race relations in literature; Slavery in literature; Racism in literature; Race in literature; Roman américain -- 19e siècle -- Histoire et critique; Métissage dans la littérature.; Roman hispano-américain -- 19e siècle -- Histoire et critique; Littérature comparée -- Américaine et hispano-américaine.; Littérature comparée -- Hispano-américaine et américaine.; Métis dans la littérature [Annulée]; Relations raciales dans la littérature.; Esclavage dans la littérature.; Racisme dans la littérature.; Race dans la littérature.; LITERARY CRITICISM -- American -- General; American fiction; Miscegenation (Racist theory) in literature; Race in literature; Race relations in literature; Multiracial people in literature; Racism in literature; Slavery in literature; Spanish American fiction; Rassenvermenging; Letterkunde; Spaans; Amerikaans; Amerika; American fiction -- 19th century -- History and criticism; Miscegenation in literature; Spanish American fiction -- 19th century -- History and criticism; Comparative literature -- American and Spanish American; Comparative literature -- Spanish American and American; Racially mixed people in literature; Race relations in literature; Slavery in literature; Racism in literature; Race in literature; 1800-1899; Criticism, interpretation, etc